Website-based food ordering information system for UMKM - Hendi Rahadiansyah; Lukman Junaedi (Institute of Computer Science (IOCS), 2024)
This research aims to help MSMEs or Micro, Small and Medium Enterprises implement their business into digital, the author will examine GISAGIS.ID MSMEs with the topic